Treatment of chronic hepatitis C-associated cryoglobulinemia vasculitis at the era of direct-acting antivirals. (July 2020) - Comarmond, Cloé; Cacoub, Patrice; Saadoun, David
Hepatitis C virus (HCV) infection is responsible for both hepatic and extrahepatic manifestations. Before the era of direct-acting antivirals (DAA), cryoglobulinemia was related to HCV infection in 70–90% of cases. Observed in 30% to 40% of patients with hepatitis C, mixed cryoglobulinemia is mainly asymptomatic. Conversely, symptomatic cryoglobulinemia vasculitis (CV) can occur in 5–10% of patients with HCV-associated cryoglobulinemia. CV is a small-vessel systemic vasculitis, and organ damage results from circulation and precipitation of cryoglobulins and complement activation. A wide range of clinical symptoms can be observed during CV, and manifestations are potentially life-threatening. The most frequent manifestations occurring in CV are cutaneous, with recurrent purpura, articular with joint pains, neurologic with peripheric neuropathy, and renal with membranoproliferative glomerulonephritis. DAA have drastically changed chronic HCV therapy. DAA induce sustained virological response (SVR) rates greater than 95%, and also improve extrahepatic manifestations such as CV. We review recent studies investigating the clinical and immune effects of DAA therapy on HCV-CV.